Impact of Health Education Program on Health Status of Heart Failure Patients: A Quasi-Experimental Study - Younus Khudhur1, Yousif Mohammed1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Heart failure, is a major cause of morbidity and mortality, especially in ageing people, it affects and kills a large number of people. Objective: The study aims to evaluate the effectiveness of an education program on the health status of patients suffering heart failure. The study design is quasi-experimental. The patients were allocated into either the experimental group ( taking the program, n = 200) or the control group (not taking the program, n= 200). The extent of samples knowledge about the disease was tested at both the pre and post education stages. A structured teaching program for imparting knowledge on various aspects of nutritional status was developed based on an extensive review of the literature and expert opinion. The results of the study were elicited based on two statistical approaches, first, descriptive statistics and the second is an inferential statistical analysis. The shows that health status sub main domains at pre-period in case and control groups was non significant, while the health status sub main domains at post period in both groups were high significant. Regarding the study global main domains in both groups along pre-post period were high significant.